2017
DOI: 10.1016/j.envpol.2016.10.085
|View full text |Cite
|
Sign up to set email alerts
|

Trace element reference intervals in the blood of healthy green sea turtles to evaluate exposure of coastal populations

Abstract: Exposure to essential and non-essential elements may be elevated for green sea turtles (Chelonia mydas) that forage close to shore. Biomonitoring of trace elements in turtle blood can identify temporal trends over repeated sampling events, but any interpretation of potential health risks due to an elevated exposure first requires a comparison against a baseline. This study aims to use clinical reference interval (RI) methods to produce exposure baseline limits for essential and non-essential elements (Na, Mg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 48 publications
7
63
2
2
Order By: Relevance
“…1), suggesting that any correlations observed with toxic elements are a result of past exposure and not due to changes in food intake or from tissue mobilization during the nesting season. These results add to the existing literature regarding accumulation and the potential effects of toxic elements on marine turtle health (Day et al, 2007;Innis et al, 2008;Komoroske et al, 2011;Register, 2011;Camacho et al, 2013;Villa et al, 2017;Ley-Quiñónez et al, 2017;Perrault et al, 2017).…”
Section: Discussionsupporting
confidence: 59%
“…1), suggesting that any correlations observed with toxic elements are a result of past exposure and not due to changes in food intake or from tissue mobilization during the nesting season. These results add to the existing literature regarding accumulation and the potential effects of toxic elements on marine turtle health (Day et al, 2007;Innis et al, 2008;Komoroske et al, 2011;Register, 2011;Camacho et al, 2013;Villa et al, 2017;Ley-Quiñónez et al, 2017;Perrault et al, 2017).…”
Section: Discussionsupporting
confidence: 59%
“…Previous research has shown evidence that green turtles have a high capacity to metabolize and detoxify cadmium at a high rate (Sinaei, 2016). However, SBNWR green turtles have one of the highest observed cadmium concentrations in green turtle red blood cell samples reported to date, 0.305 μg/mL in RBCs, suggesting that cadmium levels in SBNWR green turtles are abnormally high compared when compared to other green turtle studies that use whole blood (Villa et al, 2016).…”
Section: Cadmiummentioning
confidence: 82%
“…Green turtle selenium contamination represented the starkest difference in trace metals between SDB and SBNWR green turtles, suggesting that SBNWR green turtles are possibly at higher risk of selenium toxicity than SDB green turtles. Most other studies have found adult and juvenile green turtles had selenium concentrations roughly between 0.3 to 7 μg/mL in whole blood and RBC (van de Merwe et al, 2010a;Komoroske et al, 2011;Labrada-Martagon et al, 2011;Ley-Quinonez et al, 2013;Camacho et al, 2014;Villa et al, 2016), while SBNWR green turtles RBCs selenium ranged from 1.02 to 33.06 μg/mL. In many organisms, including banded water snakes (Nerodia fasciata), mallard ducks (Anus pltythynchos), and African clawed frogs (Xenopus laevis), excess selenium, without other trace element exposure, has been shown to reduce hatchling success, cause dermal damage and loss of neurological function (e.g.…”
Section: Seleniummentioning
confidence: 97%
“…White phosphorous poisoning has led to waterfowl mortality at an Alaskan firing range, but the persistent incineration of phosphorous and other chemicals over a 10‐year period at Johnston Atoll had no effect on nesting success of red‐tailed tropicbirds . Sublethal doses of military contaminants have been documented in the tissues of fish, marine invertebrates, sea turtles, birds, seagrass, and marine mammals, but without clear physiological consequences. In one of few community‐level studies, multiple indices of coral reef health declined in close proximity to unexploded ordinance at Vieques Island, Puerto Rico, but on the other hand, the same reefs do not exhibit measurable impacts from military activities at larger spatial scales .…”
Section: Preparationsmentioning
confidence: 99%